Potential neuroinvasion pathways of SARS-CoV-2: a review of the current literature. - Alarco, Rafael (2021)
Since its beginning, in December 2019, the pandemic caused by the coronavirus disease 2019 (COVID-19) has infected more than 116 millions of people. In addition to the well-documented respiratory manifestations caused by SARS-CoV-2, an increasing number of neurological and psychiatric manifestations are being reported among affected individuals and survivors. In this article we describe the potential invasion mechanisms of SARS-CoV-2 to the nervous system. On the basis of preceding studies on similar coronaviruses (MERS-CoV and SARS-CoV) and current evidence, three possible neuroinvasion routes used by SARS-CoV-2 are suggested: the transneuronal pathway (retrograde axonal pathway through the peripheral nerves), the hematogenous / lymphatic pathway (free through the blood and lymph or inside immune cells), and the digestive pathway (through disruption of the intestinal barrier). Although more research is needed in several areas, the elucidation of neuroinvasion routes and  of the neurotropic capacities of the virus, are vital to understand and treat the multiple neurological and psychiatric manifestations as well as the long-term sequelae that the infected patients may potentially develop.